Pelatihan Soft Skill Komunikasi Efektif Pada Puja Bhakti Remaja Cetiya Vijja Gana Tangerang - Wilson Liukarya; Diana Silaswara; Metta Susanti; Aldi Samara (Komunitas Dosen Indonesia, 2023)
This PKM activity was a collaboration between the Faculty of Business from Buddhi Dharma University and the Vijja Gana Adhikara Foundation. This activity has placed at the Cetiya Vijja Gana Vihara and the places located at Kotabumi, Tangerang Regency, Banten Province. The training participants who attended the training were young men and women at Cetiya Vijja Gana, and the activities has carried out over six months, with planned training activities in the form of focus group discussions, material presentations and interactive questions and answers between material providers and training participants and mentoring. The material provided was the needs requested by the Vijja Gana Adhikara Foundation at the start of the meeting, namely the communication methods available for young men and women under the guidance of the Vijja Gana Adhikara Foundation. Participants in the training are young men and women who's trained in the religious field of the Vijja Gana Adhikara Foundation. The planned output of this student creativity development activity is to improve Soft Skills in Effective Communication for young men and women at Cetiya Vijja Gana.